PENGARUH KONSENTRASI EKSTRAK ETANOL BONGGOL NANAS (Ananas comosus (L.) Merr) TERHADAP APOPTOSIS KARSINOMA SEL SKUAMOSA LIDAH MANUSIA - Fimma Naritasari; Hendri Susanto; Supriatno Supriatno (Faculty of Pharmacy, Universitas Gadjah Mada, 2010)
Squamous cell carcinoma is one of the most common malignancy in the oral cavity. Currently, cancer treatment using surgery, radiotherapy, chemotherapy and its combination. New strategy for cancer therapy is by searching herbal which can induce apoptosis. Bromelain is one of a potential anticancer agent that can induce apoptosis. Pineapple stem is one of a potential herbal medicine because of its bromelain enzyme content. The aim of this study was to investigate the relation between pineapple stem ethanol extract and apoptosis of oral tongue squamous cell carcinoma cell line. Oral tongue squamous cell carcinoma cell line was treated with three concentrations under IC50 of pineapple stem ethanol extract, including 5.000, 5.500, 6.000 µg/ml. In apoptosis test, cell stained with fluorochrome ethidium bromide and acridine orange after 24 hours incubation. Fluorescence microscope was used for counting the cell. Viable cell would be stained green and apoptotic cell would be stained yellow to orange. Probit analysis was used to determine IC50 of pineapple stem ethanol extract on Oral tongue squamous cell carcinoma cell line. Pearson analysis used to know the correlation between pineapple stem ethanol extract concentration and Oral tongue squamous cell carcinoma cell line apoptosis. The result showed that there was a positive correlation between concentration of pineapple stem ethanol extract and apoptotic cell (r=0,999, p<0,05). In conclusion, pineapple stem ethanol extract treatment induced apoptosis of oral tongue squamous cell carcinoma and the increases of pineapple stem ethanol extract concentration followed by the increase of apoptosis induction.